GLOBAL EXPERIENCE IN INVESTMENT PROJECT FINANCING: INSIGHTS FROM DEVELOPED COUNTRIES AND THE EBRD'S ROLE (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the experiences of developed countries in financing investment projects. It specifically examines the effective operational mechanisms of the banking systems in the UK, the USA, and Germany, as well as the role of the European Bank for Reconstruction and Development (EBRD) in financing green economy and long-term investment projects. The article also discusses the loans directed to Uzbekistan's economy by the EBRD, funds provided to support small businesses, and how international banking experiences can be used to improve the investment financing system. It offers suggestions for enhancing investment project financing practices.
Keywords: Investment projects, financing, EBRD, green economy, long-term loans, banking systems, developed countries, small businesses, financial mechanisms